Genome–wide association study for risk taking propensity indicates shared pathways with body mass index - Emma A. D. Clifton (Nature Portfolio, 2018)
Emma Clifton et al. report a genome-wide association study of risk taking propensity amongst UK Biobank participants. They identify 26 loci, 24 of which are novel, and use Mendelian randomisation analysis to explore the relationship between risk-taking propensity and BMI.